Museums inside out : artist collaborations and new exhibition ecologies - Rectanus, Mark W. (University of Minnesota Press, 2020)
"Museums Inside Out explores a wide range of contemporary museum practices, curatorial initiatives, and collaborative projects that are "moving out" of the museum's traditional spatial practices of archiving, exhibiting, and viewing culture. Focusing on the relationship between artists and what the author calls "the translocal," Moving Out examines the tensions among museums and urban spaces, cultural memory, digital culture, activism, the environment, and the cultural politics of the "creative economy." Rectanus argues that many museums increasingly promote social advocacy and curatorial practices that reject notions of neutrality, while simultaneously being bound up and constrained within neoliberal economies and financial interests as well as the ambitions of being a "global museum.""--